Sistem Informasi Tunggakan Pajak pada Dinas Pendapatan Pengelolaan Keuangan dan Kekayaan Daerah (DPPKKD) Kota Sabang - Azhar; Albahri, Fauzan Putraga; Syarifuddin (Computer Journal, 2023)
At the Sabang City Regional Financial and Wealth Management Revenue Service (DPPKKD), tax data management still uses simple methods with Microsoft Excel, causing data duplication and errors in presenting and searching for data. To overcome this, this research designs a web-based information system using PHP and MySQL. This research aims to design a Tax Arrears Information System to increase the efficiency and accuracy of information. Research methods include field studies, FlowMap analysis, interviews, comparative analysis, system design, and hardware and software specifications. The results of the analysis show weaknesses in the data processing process, such as large operational costs, difficulty in managing data, and vulnerability to data duplication. Designing a new system involves program menu structures, program flowcharts, Entity Relationship Diagrams (ERD), and system input/output design. The required hardware and software specifications are also explained. In conclusion, the use of information systems can increase efficiency and accuracy in managing tax arrears data in the Sabang City DPPKKD.